The Effect of Lean Manufacturing Practices and Knowledge Sharing on Defect Reduction Performance Among Production Workers at a Bicycle Factory, with a Culture of Continuous Improvement as a Mediating Variable - Ariyanta Dany Widyatna; Mahendra Wisnu Wicaksono; I Made Suparta; I Dewa Ketut Raka Ardiana (Cv. Syntax Corporation Indonesia, 2026)
This study aims to analyze the effect of Lean Manufacturing Practices and Knowledge Sharing on Defect Reduction Performance in bicycle factory production employees with Continuous Improvement Culture as a mediating variable. This study uses a quantitative approach with an associative research type. The research sample amounted to 290 production employees determined based on the number of indicators multiplied by 10. Data collection was carried out through a questionnaire with a Likert scale of 1–5. The data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that Lean Manufacturing Practices had a positive and significant effect on Defect Reduction Performance with a p-value of 0.000. Knowledge Sharing did not have a significant effect on Defect Reduction Performance with a p-value of 0.572. Lean Manufacturing Practices have a positive and significant effect on Continuous Improvement Culture with a p-value of 0.000. Knowledge Sharing also had a positive and significant effect on Continuous Improvement Culture with a p-value of 0.000. Continuous Improvement Culture has a positive and significant effect on Defect Reduction Performance with a p-value of 0.012. The mediation results show that Continuous Improvement Culture mediates the influence of Lean Manufacturing Practices and Knowledge Sharing on Defect Reduction Performance with a p-value of 0.022 each. This finding indicates that defect reduction is more effective when lean practices and knowledge sharing are supported by a culture of continuous improvement.